Computer Vision Syndrome in Undergraduate and Medical Students During the COVID-19 Pandemic - Wang C; Joltikov KA; Kravets S; Edward DP (Clinical Ophthalmology, 2023)
Catherine Wang,1 Katherine A Joltikov,1,2 Sasha Kravets,2,3 Deepak P Edward2,4 1University of Illinois at Chicago College of Medicine, Chicago, IL, USA; 2Illinois Eye and Ear Infirmary, Department of Ophthalmology and Visual Sciences, University of Illinois at Chicago, Chicago, IL, USA; 3Division of Epidemiology and Biostatistics, School of Public Health, University of Illinois at Chicago, Chicago, IL, USA; 4Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore, MD, USACorrespondence: Deepak P Edward, Illinois Eye and Ear Infirmary, 1009 S Wood St, Chicago, IL, 60612, USA, Tel +1 312 996 6590, Fax +1 312 996 4255, Email deepedwa@uic.eduPurpose: The purpose of this study was to evaluate Computer Vision Syndrome (CVS) in undergraduate and medical students since transitioning to online learning during the COVID-19 pandemic.Patients and Methods: This was a cross-sectional single center survey-based study using a validated CVS questionnaire (CVS-Q). The survey was distributed to 20,080 undergraduate students and 680 medical students at the University of Illinois at Chicago. The primary outcome measures were prevalence of CVS (based on CVS severity score of 6 or more), frequency of CVS and intensity of CVS symptoms.Results: The survey was completed by 2300 undergraduate students (11.4% response rate) and 154 medical students (22.6% response rate). The prevalence of CVS was 77.1% in undergraduate students and 69.1% in medical students. CVS-Q severity scores were highest for headaches and eye dryness, with over half of students reporting worsening of symptoms since March 2020. Increased time spent on online learning (undergraduate: P < 0.001, medical: P = 0.018), blue light glasses usage (undergraduate: P < 0.001, medical: P = 0.0015), and increased number of device usage were associated with higher CVS severity scores (undergraduate: P < 0.001, medical: P = 0.0032).Conclusion: CVS among undergraduate and medical students has increased since the start of the COVID-19 pandemic. More focus should be placed on the management of CVS for students in higher education. Physicians should be cognizant of the consequences of online learning and be proactive about providing advice regarding preventative measures.Keywords: digital eye strain, screen time